2017
DOI: 10.1002/ajmg.a.38370
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic FGFR3 and Biallelic ALPL mutations in a Thai girl with hypochondroplasia and hypophosphatasia

Abstract: Skeletal dysplasias are a complex group of more than 350 disorders with phenotypic and genotypic heterogeneity affecting bone and cartilage growth. We studied a 2-year-old girl and her 21-year-old mother with disproportionate short stature. In addition to typical features of hypochondroplasia found in both patients, the child had deformities of the extremity bones, metaphyseal flares, and bilateral transverse (Bowdler) fibular spurs with overlying skin dimples detected at birth. Intravenous pamidronate was sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Thus, c.984_986del may reduce the enzymatic activity too. c.1460C>T (p.A487V) and c.1466G>C (p.C489S) were reported early, of which the latter one exhibited a diminished ALP activity, less located on the cell surface and failed to become the mature form (Satou et al, 2012;Porntaveetus et al, 2017). This suggested that p.487-489 of ALPL protein may play an important role in enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, c.984_986del may reduce the enzymatic activity too. c.1460C>T (p.A487V) and c.1466G>C (p.C489S) were reported early, of which the latter one exhibited a diminished ALP activity, less located on the cell surface and failed to become the mature form (Satou et al, 2012;Porntaveetus et al, 2017). This suggested that p.487-489 of ALPL protein may play an important role in enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, c.984_986del may reduce the enzymatic activity, too. c.1460C > T (p.A487V) and c.1466G > C (p.C489S) were reported early, of which the latter one exhibited a diminished ALP activity, less located on the cell surface and failed to become the mature form [21,22]. This suggested that p. 487-489 may play an important role in enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral blood leucocytes were subjected to extraction of genomic DNA. The DNA sample was prepared according to previous publications (Porntaveetus, Srichomthong, Suphapeetiporn, & Shotelersuk, ). Sequencing was performed at Macrogen, Inc. (Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%